Pendampingan Pegembangan Budidaya Tanaman Hidroponik pada Masyarakat Desa - Jumrianah, Jumrianah (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
This community service aims to develop hydroponic plant cultivation in Masalap Raya Village, in order to improve technology-based agricultural skills and support the economic sustainability of the local community. This service design uses a participatory and practical approach, or commonly known as Pactipatory Action Research (PAR). This mentoring program is implemented through several stages, starting from basic hydroponic technique training, direct field practice, to evaluation to assess progress and provide further support. The results of this program show that the majority of participants successfully applied hydroponic techniques and obtained the first results from the plants they cultivated. Participants also demonstrated significant improvements in knowledge and skills in managing hydroponic systems. However, several obstacles related to system maintenance and business management are still faced. For this reason, further support in the form of counseling and training related to agricultural business management and marketing of hydroponic products is provided to the community. This program is expected to have a positive impact on improving agricultural skills, efficient management of agricultural businesses, and the economic welfare of the people of Masalap Raya Village.